Effect of replacing fish meal with black soldier fly larvae meal on growth performance and economic efficiency of Nile tilapia - Ouko, Kevin O.; Mboya, Jimmy B.; Mukhebi, Adrian W.; Obiero, Kevin O.; Ogello, Erick O.; Munguti, Jonathan M.; Tanga, Chrysantus M. (Fundamental and Applied Agriculture, 2024)
This study evaluated the effect of replacing fish meal (FM) with black soldier fly (Hermatia illucens) larvae meal (BSFLM) on growth performance and economic efficiency of Nile tilapia (Oreochromis niloticus) production. The BSFLM replaced FM at 0, 25, 50 and 75% (T1, T2, T3, and T4, respectively). One thousand two hundred (1,200) all-male Nile tilapia fry were stocked in twelve hapas at Kenya Marine and Fisheries Research Institute (KMFRI), Sangoro aquaculture research station in Kenya, and hand-fed four times daily for 21 weeks. Thirty (30) fish were sampled biweekly from each hapa for measurement of total length and weight. Findings indicated that diet T3 outperformed all the other diets in respect to final body weight (23.20 ± 1.15 g), daily weight gain (0.13 ± 0.02 g), final weight gain (23.09 ± 1.15 g), survival rate (96.74 ± 3.18 %), SGR (1.31 ± 0.03 % day-1), FCR (1.57 ± 0.02), feed efficiency (0.64 ± 0.02), and condition factor (1.92 ± 0.01). The cost per kilogram of feed was highest for control diet (USD 0.91) and lowest for 75% BSFLM diet (USD 0.79). Economic Conversion Ratio (ECR) was lowest for the 50% BSFLM diet (1.26 ± 0.14) and highest for the control diet (1.44 ± 0.14). Economic Profit Index (EPI) was highest for the 50% BSFLM diet (141.82 ± 7.88) and lowest for the 25% BSFLM diet (106.64 ±6.63). The findings reveal that 50 to 75% BSFLM inclusion is an ideal replacement for FM in Nile tilapia diets, and is technically and economically efficient for Nile tilapia production.